Political Affinities and Maneuvering of Soviet Political Elites: Heorhii Shevel and Ukraine's Ministry of Strange Affairs in the 1970s. Issue 3 (18th June 2019) - Bertelsen, Olga
Abstract: This article examines the goals and practices of the Ministry of Foreign Affairs in Ukraine in the 1970s, a Soviet institution that functioned as an ideological organ fighting against Ukrainian nationalists domestically and abroad. The central figure of this article is Heorhii Shevel who governed the Ministry from 1970 to 1980 and whose tactics, strategies, and practices reveal the existence of a distinct phenomenon in the Soviet Union—the nationally conscious political elite with double loyalties who, by action or inaction, expanded the space of nationalism in Ukraine. This research illuminates a paradox of pervasive Soviet power, which produced an institution that supported and reinforced Soviet "anti-nationalist" ideology, simultaneously creating an environment where heterodox views or sentiments were stimulated and nurtured.